Optimizing the Role of Family Nurses in Improving Community Health A Holistic Approach: Literature Review - Hijrah, Hijrah; Norma Lala, Nur Syamsi; Datu, Natalia; Ruben, Sethiana Dewi; Wang, Shao Ling (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Community health is an important foundation in improving the quality of life of the community as a whole. Family caregivers are the vanguard in promoting health, preventing disease, and empowering families to be agents of change. A holistic approach focusing on physical, emotional, social, and environmental aspects has optimised community health outcomes. This study aims to analyze a wide range of literature on family nursing interventions with a holistic approach to improving community health. Methods: This study uses a systematic literature review method. The studied articles were obtained from electronic databases such as PubMed, Scopus, and CINAHL, with a publication range between 2015 and 2025. The keywords include family nursing, community health, holistic approach, and nursing intervention. Selection was made based on inclusion criteria: empirical research articles, a focus on the role of family caregivers, and the application of a holistic approach. A total of 35 selected articles were analyzed using a narrative synthesis approach to identify key themes. Results: The study shows that a holistic approach in family nursing practice consistently contributes to improved healthy living behaviours, family-based management of chronic diseases, and increased access to primary health services. Key success factors include strengthening therapeutic relationships between nurses and families, using empathy-based communication, and actively involving families in the health decision-making process. Conclusions: This literature review reinforces the evidence that optimizing the role of family caregivers through a holistic approach can improve community health effectively and sustainably. To support the sustainability of these practices, there is a need for specialized training for family nurses and the integration of family-based strategies in community health policies.